Fusarium mangiferae localization in planta during initiation and development of mango malformation disease. (13th December 2016) - Cohen, Y.; Belausov, E.; Maymon, M.; Elazar, M.; Shulman, I.; Saada, D.; Shtienberg, D.; Freeman, S.
Abstract : Mango malformation disease (MMD), caused by Fusarium mangiferae, is a major constraint to mango production, causing significant yield reduction resulting in severe economic impact. The present study characterizes fungal localization in planta during initiation and development of vegetative and floral malformation. Young mango trees were artificially inoculated with a green fluorescent protein (GFP)‐expressing strain of F. mangiferae . Shoots and buds were sampled periodically over a period of more than a year and localization of the GFP‐expressing fungi was determined using confocal microscopy. Fungal localization appears to be epiphytic: mycelia remained in close contact with the plant surface but did not penetrate the tissue. In vegetative malformation and in young inflorescences, the fungus was confined to protected regions between scales, young leaf bases and buds. Fungal colonization was only very rarely detected on open leaves or on exposed shoot sections. In developed flowers, mycelia were localized mainly to protected regions at the base of the flower organs. Upon development of the inner flower organs, specific mycelial growth occurred around the anthers and the style. Mycelial penetration through the stylar tract into aborting carpels was observed. For several months, mycelia were confined to the surface of the organs and were not detected within plant tissues. Only at later stages, transient saprophytic growth of the fungus was detected causing the malformed inflorescences to senesce and collapse, concurrent with dispersion of conidia. Implications of the present study on MMD in natural field infections are discussed.